Spirituality in Christian Transhumanism: Commentary on Cole-Turner, Green, and Cannon. Issue 2 (2nd April 2016) - Ham, Sandra A.
ABSTRACT: Christian transhumanism is the growing movement in which Christians appropriate the transhumanist vision of human technological evolution in the twenty-first century for millennialist ends. In the April 2015 issue of Theology and Science, three Christian transhumanist theologians present their visions and arguments for why Christians should accept transhumanism. I draw upon the wisdom of age from the World War II generation. Their concerns about an erosion of trust that decreases quality of life guide my commentary on the theological papers. Identifying issues with vision, theology, values, character, messaging, and leadership, I present spirituality as potentially supporting future wisdom.